ÓSPIRIMLIK DÁWIRINDEGI OQÍWSHÍLARDA ÓZLESTIRMEWSHILIKTIŃ PSIXOLOGIYALÍQ SEBEPLERI - Sh.Sherimbetova, Z. (FAN va JAMIYAT, 2023)
The article analyzes the psychological characteristics of underachieving schoolchildren in adolescence. The article provides recommendations and advice on working with underachieving students.